HOT: A height optimized trie index for main-memory database systems - Binna, Robert; Zangerle, Eva; Pichl, Martin; Specht, Guenther; Leis, Viktor (Proceedings of the ACM SIGMOD International Conference on Management of Data, 2018)
We present the Height Optimized Trie (HOT), a fast and spaceefficient in-memory index structure. The core algorithmic idea of HOT is to dynamically vary the number of bits considered at each node, which enables a consistently high fanout and thereby good cache efficiency. The layout of each node is carefully engineered for compactness and fast search using SIMD instructions. Our experimental results, which use a wide variety of workloads and data sets, show that HOT outperforms other state-of-the-art index structures for string keys both in terms of search performance and memory footprint, while being competitive for integer keys. We believe that these properties make HOT highly useful as a general-purpose index structure for main-memory databases.
CRIS-Team Scopus Importer:2021-04-12
Keywords: Height optimized trie; Index; Main memory; SIMD